Cytogenetic studies in two geographical stocks of Heteropneustes fossilis (Bloch) - KUSHWAHA, B; NAGPURE, N S; SRIVASTAVA, SATISH K; PONNIAH, A G (The Indian Journal of Animal Sciences, 2014)
Studies have been undertaken in two morphologically different stocks of Heteropnuestesfossilis from distinct geographiclocations, to detect differences at chromosomal level using conventional karyotyping and NOR banding. The diploidchromosome was 2n=56 with chromosomal formula = 14m+20sm+1 2st+10t (FN=90). Prominent NOPs were located onshort arm of 1 pair of submetacentric chromosome number 12 in both the stocks and no variation in karyomorphology andNOR band pattern has been found between 2 stocks.